Sobre la síntesis de la indigotina a partir de ácido N-(Carboximetil)-Antranílico - Buehler, M.F.; López, Rodolfo; Mitta, A.E.A. (Comisión Nacional de Energía Atómica (CNEA), 1966)
Fil:Buehler, M.F. Comisión Nacional de Energía Atómica (CNEA). República Argentina